Dynamics of the endoplasmic reticulum and other membranous organelles in growth cones of cultured neurons - Dailey, ME (J Neurosci, 1989)
The fluorescent lipophilic dye 3,3′-dihexyloxacarbocyanine iodide [DiOC6(3)] was used to examine the distribution of membrane-bound organelles in growth cones of cultured rat sympathetic neurons. Within chemically fixed growth cones, intense DiOC6(3) fluorescence was localized predominately to the base or central region of growth cones. However, in most growth cones several thin DiOC6(3)-fluorescent processes radiated from the base into the periphery, and double fluorescence imaging of single growth cones indicated that these processes were highly colocalized (approximately 79%) with microtubules. The distribution of DiOC6(3) fluorescence in living growth cones was examined using low light-level fluorescence video microscopy. We observed thin fluorescent processes within the periphery of growth cones to undergo length excursions (extension/retraction) and to change orientation (move laterally). During growth cone advance, processes became progressively thicker and were gradually engulfed by the advancing fluorescent mass. When growth cones were viewed with video-enhanced differential interference contrast microscopy, the position of the fluorescent processes correlated with thickened extensions of central-type cytoplasm through which vesiclelike organelle transport often occurred. These observations indicate several features concerning the organization and movement of membranous organelles (MOs) in growth cones: (1) MOs are highly compartmentalized, the majority being localized to the growth cone base; (2) MOs advance into the periphery along distinct pathways probably associated with microtubules; (3) one or more thin continuous MOs, which most likely represent a thin tubular component of the endoplasmic reticulum, generally precedes advance of vesiclelike MOs along individual transport pathways; and (4) transport pathways with their associated MOs are spatially and temporally dynamic.